THE INTEGRATION OF RELIGIOUS CHARACTER EDUCATION IN LEARNING AT MTS SWASTA MIFTAHUL HUDA TUGU AGUNG LEMPUING - Ifrohan, Ifrohan; Nasution, Nasution; Marlena, Reni; Ristia, Muhib Ali Hasan (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2025)
This study aims to analyze and explore how religious character education is integrated into the learning process at Miftahul Huda Tugu Agung Lempuing Private Junior High School. Religious character education plays an essential role in shaping students' morals and ethics and supporting the formation of a strong religious identity. This research uses a qualitative approach with a case study method to understand the curriculum implementation and extracurricular activities that support the integration of religious character education. Data were collected through interviews with teachers, the head of the school, and students, as well as direct field observations. The findings show that Miftahul Huda Private Junior High School integrates religious character education by incorporating religious values into every subject and through regular activities such as congregational prayers, Quran memorization (tahfidz), and religious study sessions. Although challenges exist in implementing this approach, such as limited resources and varying levels of student understanding, integrating religious character has proven effective in strengthening students' character development. This study is expected to contribute to developing more applicable and effective models of religious character education in madrasahs.